Airway Obstruction Caused by Hemorrhage: Managing a Life-Threatening Complication in Patients With Acquired Hemophilia A. Issue 3 (1st February 2020) - Endermann, Susann; Korte, Wolfgang; Filipovic, Miodrag
Abstract : A 60-year-old woman presented with extensive swelling in the throat and impending airway obstruction. Following a well-established 2-step flexible bronchoscopic intubation procedure, a computed tomography scan identified a large hematoma compromising the airway. Laboratory testing confirmed the diagnosis of acquired hemophilia A (AHA), a rare condition that can potentially be life-threatening, particularly when it results in airway obstruction. The risk of fatal bleeding is substantial when difficult airway management guidelines call for a surgical airway. This case report describes the essentials of hemostatic treatment of AHA and our approach to the management of a difficult airway.